Pengaruh Edukasi Kesehatan Terhadap Kesiapan Menghadapi Menarche Pada Siswi Mi Thoriqotululum - Catur Yuliani, Feri; Kusumawati Priyono, Putri; Zuliyani, Fitri (Universitas Muhammadiyah Klaten, 2025)
The background to this research includes that female students experience development from childhood to adolescence which is marked by physical changes and the start of the reproductive system becoming active, one of the signs of which is menarche. Female students who are not ready to face menarche can cause negative reactions in the form of anxiety, fear, surprise, worry, confusion and restlessness. One effort to increase readiness is through health education about menarche. The aim of this research is to determine the effect of health education about menarche on readiness to face menarche among female MI Thoriqotul Ulum Tlogoharum students. This research uses an experimental method with a pre-experimental research design. The number of samples was 20 female students. The research instrument used a questionnaire. The data analysis technique uses Wilcoxon univariate and bivariate analysis. The research results showed that the majority of female students were 11 years old (55%), the Wilcoxon test results showed that the majority of female students were well prepared, namely 16 female students (80%), and in the moderate readiness category 4 female students (20%) with a Wilcoxon correlation coefficient of 3.923 with significance. 0.000<0.05. Research Conclusion: There is an influence of health education about menarche on the readiness to face menarche among female MI Thoriqotul Ulum Tlogoharum students. Keyword: Education, Readiness, Menarche